Late‐midlife lifestyle and brain and cognitive changes in individuals on the AD versus non‐AD continuum - Julie E. Oomens; Karly A. Cody; Lianlian Du; Erin M. Jonaitis; Rachel L. Studer; Nathaniel A. Chin; Sebastian Köhler; Pieter Jelle Visser; Stephanie J. B. Vos; Rebecca E. Langhough; Willemijn J. Jansen; Sterling C. Johnson (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION We investigated whether a composite measure of late‐midlife lifestyle was associated with (1) longitudinal brain changes and (2) cognitive changes when adjusting for these brain changes. METHODS We used linear mixed models to examine whether the LIfestyle for BRAin Health (LIBRA) index was associated with changes in tau, white matter hyperintensity, neurodegeneration, and cognition and whether changes were similar in amyloid positive (A+; > 17 Centiloids) and negative participants. RESULTS We included 324 individuals from the Wisconsin Registry for Alzheimer's Prevention (39% apolipoprotein E [APOE] ε4 carrier, 30% A+, prior baseline age 67 [50–75]). The LIBRA index was not associated with biomarker trajectories or the primary cognitive composite outcome trajectory. There were inconsistent effects on secondary domain‐specific cognitive trajectories. In contrast, tau and neurodegeneration were strongly associated with cognitive trajectories. DISCUSSION In the age‐range and disease‐range studied, lifestyle did not exhibit a meaningful effect on Alzheimer's disease or vascular biomarker accumulation and was not consistently associated with cognitive trajectories. Highlights In this age‐range, the LIfestyle for BRAin Health (LIBRA) index was not associated with biomarker trajectories. The LIBRA index was not consistently associated with cognitive trajectories. Effects of lifestyle, if any, may take more time to manifest.